Enhanced photocatalytic performance of Z-scheme N-doped Ag2CO3/GO (AGON) for microcystin-LR remediation under visible light. (February 2021) - Fan, Gongduan; You, Yifan; Yan, Zhongsen; Xia, Mingqian; Hong, Liang; Du, Banghao; Luo, Jing; Pang, Heliang
Graphical abstract: Highlights: The N-doped photocatalyst showed superior visible-light photocatalytic activity. High degradation of MC-LR was achieved by AGON/1–30 under visible light. Impact factors and possible degradation pathways of MC-LR were studied. Z-scheme mechanism was proposed to explain MC-LR degradation. Abstract: A novel Z-scheme Ag2 CO3 -NG heterojunction photocatalyst by employing N-doped graphene (NG) was successfully synthesized with enhanced photocatalytic activity for microcystin-LR (MC-LR) degradation. Characterization results suggested that doping of N can promote the nucleation and crystallization of Ag2 CO3 . Photocatalytic tests showed that Ag2 CO3 -NG with 30 wt.% N-participation (AGON/1–30) showed the best photocatalytic performance under visible-light irradiation, which could remove MC-LR in 7.5 min, superior to Ag2 CO3 -GO composite. Multiple factors including dosage, pH value, MC-LR concentration, H2 O2, and the coexistence of Microcystis aeruginosa were studied to reveal the environmental impact on MC-LR degradation. Results showed that ·OH, ·O2 −, as well as ·CO3 − were the main ROSs in MC-LR degradation. The excellent reusability and stability of AGON/1–30 were proved through five consecutive cycles of degradation. Therefore, the Z-scheme Ag2 CO3 -NG heterojunction photocatalyst is a promising technique for MC-LR remediation.